Conocimientos, actitudes y prácticas en madres; sobre estimulación y cuidado en neonatos prematuros del Área Neonatología del Hospital Isidro Ayora Loja - Sánchez Bustamante, Tania Beatriz (2015)
The care and stimulation of the premature neonate, it constitutes the fundamental base in the reduction of the morbi-mortality perinatal as in the prevention of physical and neurological complications, at the same time that it favors a development sensorineural suitably similar or equally to the newborn baby to term. The present descriptive work, of quantitative nature, was faced to characterize the knowledge, attitudes and practices that the mothers have, with regard to the care and stimulation of the Premature Newborn babies who remain in the field of Neonatology of the General Hospital “Isidro Ayora“, of the city of Loja, in the period July, 2014 – August, 2015. The universe was shaped by 30 mothers of the above mentioned children, hospitalized during June. A questionnaire of 27 questions was applied, to determine the knowledge, the attitudes and practices of the mothers in the care and stimulation of the premature neonate. The obtained results appeared in simple stage expressed in frequency and percentage, with the consequent data analysis and formulation of conclusions and recommendations. It being obtained like result that most of the mothers have ignorance and they develop inadequate practices in the care of the premature baby. Likewise they do not know the skills and the main areas of stimulation of the premature baby. The obtained results to constitute a basic element, which might serve as base in the construction and adaptation of a guide of care to the neonate which can help to strengthen the knowledge of the mothers in the care and stimulation of the premature baby, this way contributing to the integral development of the premature neonate. KEY WORDS: Premature baby, neurodesarrollo, confrontation, aftermath, care.